Breast satisfaction in adult women with Turner syndrome—An international survey employing the BREAST‐Q questionnaire. (25th May 2022) - Idkowiak, Jan; Smyth, Arlene; Mundy, Lily; Wanaguru, Amy; Gleeson, Helena; Högler, Wolfgang
Abstract: Objective: Turner syndrome (TS) is associated with short stature, delayed puberty, primary ovarian insufficiency, and other features. Most girls with TS require oestrogen replacement for pubertal induction. There is paucity of data in adult TS on pubertal outcomes, including breast satisfaction. Here, we assess breast satisfaction in TS with the BREAST‐Q questionnaire, a well‐validated patient‐related outcome measure (PROM). Design: International survey distributed online through TS support groups. Patients: Adult women aged 18–45 years with TS (self‐reported). Measurements: The questionnaire contained demographics, health history and the four domains of the BREAST‐Q. BREAST‐Q scores were matched on a one‐to‐one basis for age, body mass index (BMI) and educational background to a normative data set derived from the 'Army of Women', an online community of healthy volunteers. Results: Of 97 total responses, 74 could be matched to the control cohort. Median age was 32 years (18–45 years) and 97% were White Caucasian. Median age at menarche was 15.5 years (12–34 years), 86% had received pubertal induction therapy as teenagers. We found significantly lower BREAST‐Q scores in TS in the domains 'Satisfaction with Breast' ( p = .021), 'Psychosocial Wellbeing' ( p < .0001) and 'Sexual Wellbeing' ( p < .0001). TS who had received oestrogen replacement therapy reported lower scores compared to TS who had not received oestrogen therapy ( p < .0001). Lower BMI and previous growth hormone therapy were associated with lower breast satisfaction. Conclusions: TS women who received oestrogen replacement for pubertal induction self‐report lower breast satisfaction scores and late menarche, suggesting that type, mode of delivery, dose and timing of hormone supplements merit prospective study.